The prevalence and risk factors of Helicobacter pylori infection and cagA virulence gene carriage in adults in the Navajo Nation - D. Pete; N. Salama; J. Lampe; M Wu; A. Phipps (Microbiota in Health and Disease)
Objective: American Indian and Alaska Native people in the United States experience high rates of stomach cancer. Helicobacter pylori infection is a significant risk factor for stomach cancer, and H. pylori strains that carry the cagA gene are linked to greater gastrointestinal disease severity. Yet, little is known about H. pylori and cagA infections in American Indian and Alaska Native people, particularly at the tribal level. We assessed the prevalence and risk factors of H. pylori infection and cagA gene carriage in tribal members from the Navajo Nation.